Ductal Carcinoma in Situ in Ireland, 2008-2020: Screening Data related to Low-Risk Management Trials. (20th October 2021) - Kelly, C; Fitzpatrick, P; Quinn, C; Flanagan, F; Connors, A; Larke, A; Mooney, T; O'Doherty, A
Abstract: Background: Four clinical trials are on-going to determine if active surveillance is a feasible management option for patients with low-risk ductal carcinoma in situ (DCIS), in response to concerns that breast cancer screening programmes have increased the incidence of DCIS, some of which may never progress to invasive cancer. This study aimed to describe the epidemiology of screen-detected DCIS in Ireland through the BreastCheck, the national breast screening programme in Ireland (commenced 2000 but fully national since 2008). Methods: This was a cross-sectional analysis of anonymised BreastCheck data provided by the National Screening Service, including all cases of screen-detected DCIS between 2008 and 2020. Statistical tests included Mann-Whitney U, Chi square, and multivariable logistic regression. Results: 2, 240 women were diagnosed with DCIS through BreastCheck between 2008 and 2020 (1353 (60.4%) high-grade and 876 (39.1%) low/intermediate grade). The overall rate of screen-detected DCIS incidence has remained relatively stable during this time. Women with high- grade DCIS were older than women with low/intermediate DCIS (57 (IQR 53-61) years v 56 (IQR 56-61) years; p < 0.001). They were also more likely to have been diagnosed at a subsequent screening episode than at an initial episode (71.0% v 57.5%; p < 0.001). After adjustment (deprivation score, screening unit and year) the odds ratio for high-grade was 1.62 (95% CI 1.30-2.03; p < 0.001) for subsequent compared with initial screening episode. Conclusions: When trial results are available, these data will assist with service planning should active surveillance be approved as a management option. Based on trial inclusion criteria, up to 40% of women diagnosed with DCIS through BreastCheck may be eligible for consideration for active surveillance. These women are younger and often diagnosed on initial screening episode, so may require longer active follow-up. Key messages: Majority of DCIS in national screening programme is high grade. Randomised controlled trial evidence will provide guidance on management of low-risk DCIS.